Teacher-Evaluated Self-Regulation Is Related to School Achievement and Influenced by Parental Education in Schoolchildren Aged 8–12: A Case–Control Study - van Tetering, Marleen A. J.; de Groot, Renate H. M.; Jolles, Jelle (Frontiers in Psychology, 2018)
There are major inter-individual differences in the school achievements of students aged 8-12. The determinants of these differences are not known. This paper investigates two possible factors: the self-regulation of the student and the educational levels obtained by their parents. The study first investigates whether children with high and low levels of academic achievement differ in their self-regulation. It then evaluates whether there are differences in the self-regulation of children with high and moderate-to-low levels of parental education (LPE). The focus was on the self-regulation of students as judged by their teacher. Teacher evaluations were assessed using an observer questionnaire: the Amsterdam Executive Functioning Inventory. Results showed that students with low levels of school achievement had substantially lower self-regulation than children with high levels of school achievement. Furthermore, self-regulation was lower for children with moderate-to-low LPE than for children with high LPE. The findings suggest that interventions on the domain of self-regulation skills should be developed and used, particularly in students at risk of poor school achievement.